2010
DOI: 10.1021/jp909787t
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Screening of −NH2-, −OH-, −CH3-, −F-, and −SH-Substituted Porphyrins As Sensitizer Candidates for Dye-Sensitized Solar Cells

Abstract: Following former studies, the donor-acceptor combinations of -NH(2)-substituted porphyrin donor and the acceptors C, D, E, F, H and G, those of -OH-, -CH(3)- and -Ph-substituted porphyrins as well as porphine donors and the acceptors E, G, and H, and those of -F- and -SH-substituted porphyrin donors and the acceptor G as novel sensitizer candidates have been designed and calculated at the density functional B3LYP level. The result shows that -NH(2)-, -OH- and -CH(3)-substituted porphyrins as donors combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…The adsorbed ZnPVB clearly shows considerable overlap with STNT states over a wide range of energies in both the VB and the CB, indicating strong electronic coupling between the two species at the interface, in good agreement with the above geometrical analysis. [29] These unoccupied adsorbate states clearly arise from a number of molecular orbitals with the LUMO character of isolated ZnPVB, originating from the energy level split of the single LUMO of ZnPVB upon its adsorption on the STNT. Of note are the introduced hybrid states in the band gap of the STNT, which are completely attributable to the adsorbed dye molecule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorbed ZnPVB clearly shows considerable overlap with STNT states over a wide range of energies in both the VB and the CB, indicating strong electronic coupling between the two species at the interface, in good agreement with the above geometrical analysis. [29] These unoccupied adsorbate states clearly arise from a number of molecular orbitals with the LUMO character of isolated ZnPVB, originating from the energy level split of the single LUMO of ZnPVB upon its adsorption on the STNT. Of note are the introduced hybrid states in the band gap of the STNT, which are completely attributable to the adsorbed dye molecule.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, before injection into the CB, the ground-state electron was first promoted to an excited state, which was confirmed by the adsorbate states in the CB of the STNT (see arrows in Figure 5). [29] These unoccupied adsorbate states clearly arise from a number of molecular orbitals with the LUMO character of isolated ZnPVB, originating from the energy level split of the single LUMO of ZnPVB upon its adsorption on the STNT. To distinguish those of the free dye molecule, the HOMO and split LUMOs of the adsorbed dye molecule are denoted as HOMOA C H T U N G T R E N N U N G (ads) and LUMOA C H T U N G T R E N N U N G (ads).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the DE (CV) value of chromophore L2 is 1.52 eV. The narrower energy gap indicated easier charge transfer [29,43]. It can be concluded that the LUMO energy of chromophore L1 is 0.016 eV lager than chromophore L2 (À3.701 eV vs.À3.685 eV), while the HOMO energy of L1 is 0.104 eV larger than that of L2 (À5.104 eV vs. À5.208 eV).…”
Section: Theoretical Calculations and Redox Propertiesmentioning
confidence: 92%
“…The frontier molecular orbitals are often used to obtain information about the optical and electrical properties of molecules [43]. Fig.…”
Section: Theoretical Calculations and Redox Propertiesmentioning
confidence: 99%